2021
DOI: 10.1101/2021.08.18.456837
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Mechanosensitive Ion Channel MSL10 Modulates Susceptibility toPseudomonas syringaeinArabidopsis thaliana

Abstract: Plants sense and respond to molecular signals associated with the presence of pathogens and their virulence factors. Mechanical signals generated during pathogenic invasion may also be important, but their contributions have rarely been studied. Here we investigate the potential role of a mechanosensitive ion channel, MscS-Like (MSL)10, in defense against the bacterial pathogen Pseudomonas syringae in Arabidopsis thaliana. We previously showed that overexpression of MSL10-GFP, phospho-mimetic versions of MSL10… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 91 publications
(140 reference statements)
0
7
0
Order By: Relevance
“…EMS-induced suppressor mutants, referred to as s uppressed d eath from m sl10-3G ( sdm ), were initially isolated based on increased height compared to parental msl10-3G plants in the M1 and M2 generations. As msl10-3G plants share some of the characteristics of lesion-mimicking-mutants (Basu et al, 2021), and intragenic mutations are particularly common in suppressor screens of lesion-mimicking mutants (van Wersch et al, 2016), we sequenced MSL10 exons in all 40 mutant lines. Indeed, 35 had a missense mutation in the MSL10 coding or splice-junction sequences ( Figure 4-figure supplement 1a ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…EMS-induced suppressor mutants, referred to as s uppressed d eath from m sl10-3G ( sdm ), were initially isolated based on increased height compared to parental msl10-3G plants in the M1 and M2 generations. As msl10-3G plants share some of the characteristics of lesion-mimicking-mutants (Basu et al, 2021), and intragenic mutations are particularly common in suppressor screens of lesion-mimicking mutants (van Wersch et al, 2016), we sequenced MSL10 exons in all 40 mutant lines. Indeed, 35 had a missense mutation in the MSL10 coding or splice-junction sequences ( Figure 4-figure supplement 1a ).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanosensitive ion channel MSL10 has been well studied using electrophysiological approaches (Haswell et al, 2008; Maksaev and Haswell, 2012; Maksaev et al, 2018). Genetic analyses have attributed a variety of roles to MSL10, like the induction of Ca 2+ transients, reactive oxygen species accumulation, enhanced immune responses, and programmed cell death (Basu and Haswell, 2020; Moe-Lange et al, 2021; Basu et al, 2021), but we lack a clear understanding of how MSL10 activation leads to these downstream signaling outcomes. Studies using multiple gain-of-function MSL10 alleles found that MSL10 signaling can trigger cell death independently of ion flux (Veley et al, 2014; Zou et al, 2016; Maksaev et al, 2018; Basu et al, 2020), though it remains unknown how this occurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant cells sense mechanical stimuli in nature, such as touch, gravity, and the stretching of membranes. MECHANOSENSITIVE (MS) ion channels that serve to sense and respond to changes in membrane tension have been known to directly couple mechanical stimuli to ion flux (Peyronnet et al, 2014;Basu and Haswell, 2017). There are a few plant MS channel families that have been reported as Ca 2+ channels (Basu and Haswell, 2017).…”
Section: Mechanosensitive-like Channelsmentioning
confidence: 99%
“…MECHANOSENSITIVE (MS) ion channels that serve to sense and respond to changes in membrane tension have been known to directly couple mechanical stimuli to ion flux (Peyronnet et al, 2014;Basu and Haswell, 2017). There are a few plant MS channel families that have been reported as Ca 2+ channels (Basu and Haswell, 2017). One of them is ECHANOSENSITIVE CHANNEL OF SMALL CONDUCTANCE (MSCS)-LIKE CHANNELs (MSLs).…”
Section: Mechanosensitive-like Channelsmentioning
confidence: 99%